Experience, cortisol reactivity, and the coordination of emotional responses to skydiving - Meyer, Vanessa J.; Lee, Yoojin; Böttger, Christian; Leonbacher, Uwe; Allison, Amber L.; Shirtcliff, Elizabeth A. (Frontiers in Human Neuroscience, 2015)
Physiological habituation to laboratory stressors has previously been demonstrated, although the literature remains equivocal. Previous studies have found skydiving to be a salient naturalistic stressor that elicits a robust subjective and physiological stress response. However, it is uncertain whether (or how) stress reactivity habituates to this stressor given that skydiving remains a risky, life-threatening challenge with every jump despite experience. While multiple components of a stress response have been documented, it is unclear whether there is an individual’s subjective emotions are related to their physiological responses. Documenting coordinated responsivity would lend insight into shared underlying mechanisms for the nature of habituation of both subjective (emotion) and objective (cortisol) stress responses. Therefore, we examined subjective emotion and cortisol responses in first-time compared to experienced skydivers in a predominantly male sample (total n = 44; males = 32, females = 12). Hierarchical linear modeling revealed that experienced skydivers showed less reactivity and faster recovery compared to first-time skydivers. Subjective emotions were coordinated with physiological responses primarily within first-time skydivers. Pre-jump anxiety predicted cortisol reactivity within first-time, but not experienced, skydivers. Higher post-jump happiness predicted faster cortisol recovery after jumping although this effect overlapped somewhat with the effect of experience. Results suggest that experience may modulate the coordination of emotional response with cortisol reactivity to skydiving. Prior experience does not appear to extinguish the stress response but rather alters the individual’s engagement of the HPA axis.